Echocardiographic assessment of the right heart in adults: a practical guideline from the British Society of Echocardiography - Abbas Zaidi; Daniel S Knight; Daniel X Augustine; Allan Harkness; David Oxborough; Keith Pearce; Liam Ring; Shaun Robinson; Martin Stout; James Willis; Vishal Sharma (Echo Research and Practice, 2020)
The structure and function of the right side of the heart is influenced by a wide range of physiological and pathological conditions. Quantification of right heart parameters is important in a variety of clinical scenarios including diagnosis, prognostication, and monitoring response to therapy. Although echocardiography remains the first-line imaging investigation for right heart assessment, published guidance is relatively sparse in comparison to that for the left ventricle. This guideline document from the British Society of Echocardiography describes the principles and practical aspects of right heart assessment by echocardiography, including quantification of chamber dimensions and function, as well as assessment of valvular function. While cut-off values for normality are included, a disease-oriented approach is advocated due to the considerable heterogeneity of structural and functional changes seen across the spectrum of diseases affecting the right heart. The complex anatomy of the right ventricle requires special considerations and echocardiographic techniques, which are set out in this document. The clinical relevance of right ventricular diastolic function is introduced, with practical guidance for its assessment. Finally, the relatively novel techniques of three-dimensional right ventricular echocardiography and right ventricular speckle tracking imaging are described. Despite these techniques holding considerable promise, issues relating to reproducibility and inter-vendor variation have limited their clinical utility to date.